Therapeutic role of columbianadin in human disorders: Medicinal importance, biological properties and analytical aspects - Dinesh Kumar Patel (Elsevier, 2023)
Introduction: Herbal medicines have been used for the treatment of human disorders and associated secondary complications since a very early age. Herbal medicines are composed with a variety of medicinal plants and their derived products. Coumarin class phytochemicals have an important role in medicine due to its anti-coagulant, anti-cancer, anti-HIV and anti-inflammatory activity. Herbal medicines have been gaining popularity in the modern system of medicine mainly due to its safety and efficacy. Columbianadin is an active phytochemical of Angelica pubescens and Heracleum candolleanum. Columbianadin have analgesic, anti-inflammatory, calcium-channel blocking properties and platelet aggregation inhibitory potential. Methods: Present work described the medicinal importance and pharmacological activities of columbianadin in medicine supported by their traditional medicinal application and pharmacological activities. Scientific data of columbianadin has been collected from PubMed, Google Scholar, Google, Scopus, and Science Direct. However, scientific data of columbianadin published in Journals, books and scientific report have also been collected in the present paper. Analytical data of columbianadin have also been described to know the significance of analytical techniques for the isolation, and identification of columbianadin. Results: Scientific data of columbianadin signified the biological importance and therapeutic potential of columbianadin in medicine. Scientific data of columbianadin revealed their biological potential against inflammation, neuropathic pain, cancer, hepatic complications, and immune system disorders. However, biological effectiveness of columbianadin on blood-brain barrier permeability, body tissue, channels and platelet has also been discussed in the present work. Moreover, its therapeutic effectiveness against nematodes has been also summarized in this work. Analytical data for the isolation and identification of columbianadin in different samples has also been presented in this work. Discussion: Present work signified the biological importance and therapeutic potential of columbianadin in medicine, which could be used for the treatment of human disorders and associated secondary complications.